Atomic cerium modulated palladium nanoclusters exsolved ferrite catalysts for lean methane conversion. Issue 6 (11th July 2022) - Yang, Yanling; Wang, Si; Tu, Xin; Hu, Zhiwei; Zhu, Yinlong; Guo, Hongquan; Li, Zhishan; Zhang, Li; Peng, Meilan; Jia, Lichao; Yang, Meiting; Yang, Guangming; et al.
Abstract: The active and stable palladium (Pd) based catalysts for CH4 conversion are of great environmental and industrial significance. Herein, we employed N2 as an optimal activation agent to develop a Pd nanocluster exsolved Ce‐incorporated perovskite ferrite catalyst toward lean methane oxidation. Replacing the traditional initiator of H2, the N2 was found as an effective driving force to selectively touch off the surface exsolution of Pd nanocluster from perovskite framework without deteriorating the overall material robustness. The catalyst showed an outstanding T50 (temperature of 50% conversion) plummeting down to 350°C, outperforming the pristine and H2 ‐activated counterparts. Further, the combined theoretical and experimental results also deciphered the crucial role that the atomically dispersed Ce ions played in both construction of active sites and CH4 conversion. The isolated Ce located at the A‐site of perovskite framework facilitated the thermodynamic and kinetics of the Pd exsolution process, lowering its formation temperature and promoting its quantity. Moreover, the incorporation of Ce lowered the energy barrier for cleavage of C─H bond, and was dedicated to the preservation of highly reactive PdO x moieties during stability measurement. This work successfully ventures uncharted territory of in situ exsolution to provide a new design thinking for a highly performed catalytic interface. Abstract : The CH4 conversion is of great environmental and industrial significance to solve the greenhouse effect. N2 as an optimal activation agent to develop a Pd nanocluster exsolved Ce‐incorporated perovskite ferrite catalyst toward lean methane oxidation. The isolated Ce locating at the A‐site of perovskite framework facilitates the thermodynamic and kinetics of the Pd exsolution process, lowering the Pd nanocluster formation temperature and promoting its quantity.